Promoting cocoa agroforestry under conditions of separated ownership of land and trees: Strengthening customary tenure institutions in Cameroon. (September 2021) - Jaza Folefack, Achille Jean; Darr, Dietrich
Abstract: Formal and customary land tenure can encourage the adoption of sustainable land management practices. Yet, certain forms of customary land tenure can deter farmers from practicing agroforestry. One such example is the case of cocoa agroforestry in the Centre region of Cameroon, where cocoa orchards and the fruit trees that grow inside were traditionally inherited separately to different family members. While customary land owners hesitate to allow tree cultivation in their cocoa orchards as they are afraid of losing out while sharing their land, the tree owners would often like to expand the number of fruit trees, but lack the land to do so. This study assessed how various policy instruments can enhance the adoption of agroforestry in this context. Using the Coase theorem, we analyzed seven agroforestry systems of cocoa in association with Safout ( Dacryodes edulis ), Bush mango ( Irvingia gabonensis ) and/or Ndjansang ( Ricinodendron heudelotii ). Land sharing with fruit producers reduced the cocoa mono-croppers' farm income by 40–80%, while fruit producers benefited especially from the cultivation of Bush mango. According to our baseline Coase theorem results, cocoa agroforestry was socially efficient when 13–60 fruit trees/ha were planted, providing a positive net social benefit (248, 753 to 3, 394, 829 FCFA/ha). The policy intervention scenarios (cocoa certification, payment from voluntary carbon projects and reform of the current customary tenure system) led to more fruit trees being planted (14–71 trees/ha) and increased the net social benefit (266, 418 to 5, 753, 595 FCFA/ha). Both farmer categories gained in each of the scenarios, with the fruit producers benefiting more than the cocoa croppers. Among the investigated policy instruments, a land tenure reform inducing a fair revenue sharing proved to be the most effective in encouraging tree planting in cocoa farms. Highlights: Separated ownership of land and trees discourages cocoa agroforestry (AF) in central Cameroon. Fruit producers gain, but cocoa croppers' farm income drops by 40–80% in AF vs. cocoa monoculture. Cocoa AF is socially efficient with 13–60 fruit trees/ha depending on species combination. Cocoa certification, PES and land reform scenarios promote AF (14–71 trees/ha) and net social benefit. Land reform with benefit sharing between both parties was most effective in absence of formal tenure rights.